Pendampingan Orang Tua ddalam Pemanfaatan Teknologi Oleh Anak Dirumah Kober Miftahul Ulum Jayasari - Esa Esa Eryani; Enung Ratna Sunaryati; Sulastri Banyutresna (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
The research objectives of assisting parents in the use of technology by children at home can include a better understanding of how parents can support the positive use of technology, involving children in educational activities, and maintaining a balance between online and offline time for optimal child development. Because technology cannot be separated from the lives of children in this increasingly sophisticated era. The existence of technology is undeniable and however children cannot be prevented or prohibited from using it, but proper control and assistance can be the right solution for children. Therefore, this study answers the problems often faced by parents and teachers. This study uses qualitative research with observation and interview techniques in the data collection process, and uses literature study methods from various journals, books, and supporting research results. The research was conducted at KOBER MIFTAHUL ULUM located in Jayasari Village, Langkaplancar District, Pangandaran Regency with 3 subjects of parents and guardians of students at KOBER MIFTAHUL ULUM. This research uses a type of qualitative research to see and understand the subject and object under study. By using observation and interview methods in the data collection process, as well as using literature study methods from various journals, books, and supporting research results. The results of this study show that the average parent guardian has not provided much control and assistance in the use of smartphones in children so that children spend more time playing smartphones than playing with their peers. Meanwhile, in the field of education, technology has not been utilized optimally by teachers. So it is hoped that the results of this research can be a reference material for teachers and parents in the process of utilizing technology.